Corporate Governance and Financial Performance: The Moderating Role of Managerial Ownership - I Kadek Bagiana; Putu Pande R. Aprilyani Dewi; Made Denny Oktaryana; Putu Ayu Anggya Agustina (Jurnal Ilmiah Akuntansi & Bisnis, 2026)
This study investigates the role of managerial ownership as a primary internal governance mechanism in moderating the impact of growth dynamics on firm profitability within a capital-intensive industry. Focusing on Indonesian energy companies listed on the Indonesia Stock Exchange during 2022–2024, the study investigates the effects of the Investment Opportunity Set (IOS) and Asset Growth (AG) on financial performance (ROA) and tests Managerial Ownership (MOWN) as a moderating variable. Using a balanced panel of 39 firms (117 firm-year observations) and applying moderated regression analysis within a panel-data framework, the estimation indicates that IOS is negatively and significantly associated with ROA, suggesting that higher market-implied growth opportunities coincide with lower contemporaneous profitability in the sampled period. In contrast, AG shows a positive and significant effect on ROA, implying that realized asset expansion is, on average, associated with improved profitability. Managerial ownership does not exhibit a significant direct effect on ROA, however it plays a contingent role through interaction effects. Specifically, MOWN weakens the negative IOS–ROA relationship and dampens the positive AG–ROA relationship, indicating that managerial equity stakes condition how growth expectations and realized expansion translate into profitability. These findings extend agency-based insights on investment efficiency in high CAPEX settings and offer practical implications for boards and investors regarding the governance conditions under which growth becomes more or less profitable.